Discursive tensions: Outcomes and rights in educators' accounts of children's relaxation. (March 2023) - Cooke, Emma; Zheng, Zhaoxi; Houen, Sandy; Thorpe, Karen; Clarke, Andrew; Oakes, Candice; Staton, Sally
In early childhood education and care policy, there are two dominant discourses: 'investment and outcomes' and 'children's rights'. There is little research on how these discourses play out in educators' accounts. In this article, the authors examine the case of discourse pertaining to children's relaxation in early childhood education and care. They demonstrate that Australian relaxation policy for children in early childhood education and care constructs children as passive and incompetent subjects. Some educators reproduce early childhood education and care policy tensions by vacillating between investment-outcomes and children's rights discourse in their accounts, while other educators deviate from the policy constructions and adopt children's rights discourse.